The Evaluation of unexpected results of a seismic hazard applied to a modern Hydroelectric center in central Ecuador - Toulkeridis, Theofilos (Journal of Structural Engineering, 2024)
At the base of Tungurahua volcano, the huge water flow volume and the high waterfalls of the Pastaza River generate the electrical energy in the San Francisco hydroelectric project (SFHP). At this level, the water flows through an 11.2 km tunnel, until the engine room, with an installed capacity of 230 MW. This area is known as a high seismic hazard, the beams and the columns that compose the building should have a specific design that take in account a particular considerations. Unfortunately, the engine room control building of the SFHP, possess beams stronger than the joints and columns. This study presents (a) design performance of the beam-column connection; (b) momentum-curvature relation of the elements obtained; (c) seismic resistance capacity of a structure obtained using the pushover technique; (d) structure performance of a pseudo-spatial seismic analysis; (e) obtaining reduction factor of the seismic forces. Based on this study, it is evidenced that the engine room control building of the SFHP, despite it modern age, is not appropriate to resist for a future seismic event.